The Electronic Service Quality and Islamic Social Finance Integration: Case Study from Kitabisa.com - Mulyandi, M. Rachman; Jonathan; Hertanto, Christofer Augusta; B Tarigan, Gabriel Denli (International Journal of Islamic Thought and Humanities, 2025)
The purpose of this research is to examine the application of electronic service quality and digital payment service integration using Islamic principles in the Kitabisa.com system. The research method used in this study is qualitative, employing observation analysis and literature study techniques. The results of this study indicate that the electronic service quality available on the Kitabisa.com application greatly facilitates users and enhances their satisfaction. Regarding payment service integration using Islamic principles, it also strongly supports donors in making digital donations. The result also states that kitabisa is a medium for strengthening social solidarity and trust between users and beneficiaries. The combination of quality technology services, ease of digital transactions, and alignment with religious values makes Kitabisa.com a successful example of Sharia-based crowdfunding that can be used as a reference for the development of social digital services in the future The obstacles in this study were the limited primary data involving active respondents from the Kitabisa.com user community, making it difficult to describe the variability of donors' attitudes and motivations comprehensively.